What Will Survive of Us? - D. Rácz, István (Hungarian Journal of English and American Studies, 2020)
Book review:Booth, James. Philip Larkin: Life, Art and Love. London: Bloomsbury, 2014. 532 pages. ISBN 978 1 4088 5166 1. Hb. £25.00.